Enoch’s revelations? - Stone, Michael E. (Journal for the study of the pseudepigrapha, 2022)
This article examines the relationship between Enoch’s ontological state and the types of information that are revealed to him. Concentrating on two Enochic works, the Book of the Watchers and the Book of Dream Visions, this question is pursued both internally, that is within the works, and in a comparative fashion. Differences were discerned in the presentation of the seer in these two works.